LEVEL OF MILLENNIUM DEVELOPMENT GOALS AWARENESS AMONG STUDENTS AT PRINCESS ALIA UNIVERSITY COLLEGE - M. Nashash, Hyam (European Scientific Journal, ESJ, 2013)
﻿The study is aimed at investigating the extent to which students at Al- Balqaa’ Applied University - Princess Alia University College are aware of the Millennium Development Goals. The descriptive survey design was adopted and the purposive sampling technique were employed to select 271 participants to respond to questionnaire items developed by the reseracher based on their knowledge. Statistical analysis of the responses using the t-test showed that awareness among students of the Millennium Development Goals is generally low. Additionally, there is statistical significant difference in the awareness of the Millennium Development Goals between students pursuing a bachelor’s degree and those pursuing a diploma, where the former are more aware of the Millennium Development Goals. Implications of these findings were discussed and it was suggested instructors should give more attention to relevant topics and that raising awareness is a task that is not confined to one stakeholder, the universities in this case, but rather requires that all stakeholders get involved in the process. Research Limitations and implications: Financial constraint has automatically re-defined the researchers’ need to expand the scope of coverage, limiting the investigation to students at Al-Balqa Applied University – Princess Alia University College. Therefore, the generalization of the study are limited to the sample of students involved